Molecular pathogenesis of polymerase gamma–related neurodegeneration. Issue 1 (14th June 2014) - Tzoulis, Charalampos; Tran, Gia Tuong; Coxhead, Jonathan; Bertelsen, Bjørn; Lilleng, Peer K.; Balafkan, Novin; Payne, Brendan; Miletic, Hrvoje; Chinnery, Patrick F.; Bindoff, Laurence A.
<x xml:space="preserve">Abstract</x> Objective Polymerase gamma (POLG) mutations are a common cause of mitochondrial disease and have also been linked to neurodegeneration and aging. We studied the molecular mechanisms underlying POLG‐related neurodegeneration using postmortem tissue from a large number of patients. Methods Clinical information was available from all subjects. Formalin‐fixed and frozen brain tissue from 15 patients and 23 controls was studied employing a combination of histopathology, immunohistochemistry, and molecular studies of microdissected neurons. Results The primary consequence of POLG mutation in neurons is mitochondrial DNA depletion. This was already present in infants with little evidence of neuronal loss or mitochondrial dysfunction. With longer disease duration, we found an additional, progressive accumulation of mitochondrial DNA deletions and point mutations accompanied by increasing numbers of complex I–deficient neurons. Progressive neurodegeneration primarily affected the cerebellar systems and dopaminergic cells of the substantia nigra. Superimposed on this chronic process were acute, focal cortical lesions that correlated with epileptogenic foci and that showed massive neuronal loss. Interpretation POLG mutations appear to compromise neuronal respiration via a combination of early and stable depletion and a progressive somatic mutagenesis of the mitochondrial genome. This leads to 2 distinct but overlapping biological processes: a chronic neurodegeneration reflected clinically by progressive ataxia and cognitive impairment, and an acute focal neuronal necrosis that appears to be related to the presence of epileptic seizures. Our findings offer an explanation of the acute‐on‐chronic clinical course of this common mitochondrial encephalopathy. ANN NEUROL 2014;76:66–81